Finding the right spot: laws governing the siting of aquaculture activities - Markus, Till (Frontiers in Aquaculture, 2024)
Marine aquaculture has grown enormously in recent decades, and with it the competition for space suitable for aquaculture. These developments have limited the areas available for aquaculture and, in some cases, have become a barrier to expansion. In response, aquaculture operations have moved further away from the coast. This development has created a need for clearer and more robust approaches to more comprehensively describe and secure sites for aquaculture. This article reviews the law governing the siting of aquaculture operations. In particular, it assesses the role of the widely used term 'offshore' in the Law of the Sea to see if there are any legal aspects that need to be considered in moving towards the use of more specific concepts. It also aims to inform scientific discussions and political and administrative processes on the law governing the identification, description, and siting of aquaculture operations. This will hopefully contribute to more sustainable and less conflicted longterm aquaculture development.